Efektivitas Senam Prolanis Terhadap Nilai Tekanan Darah Pada Penderita Hipertensi Di Puskesmas - Waode Luthfiyyah Adeline; Shinta Prawitasari; Hardin La Ramba (JURNAL KESEHATAN PRIMER, 2025)
Background: Hypertension remains a growing global health concern, especially among the elderly and working-age populations, requiring holistic management strategies. Prolanis exercise, a community-based non-pharmacological approach, was introduced to help control blood pressure in hypertensive patients. Objective: This study evaluated its effectiveness at Tanjung Priok Health Center using a quantitative pretest-posttest design without a control group. Fifty-seven randomly selected participants engaged in two 30-minute exercise sessions over one month. Method: Blood pressure was measured before and after, and data were analyzed using the Wilcoxon test. Results: Showed no significant differences in systolic or diastolic blood pressure (p-values: 0.763 and 0.071). Most respondents were elderly, female, and unemployed. The study's limitations include low intervention frequency and lack of analysis on psychosocial and cultural factors. Future studies should employ more intensive and culturally sensitive approaches to improve outcomes.